THE EFFECT OF COMPETENCY IMPROVEMENT AND TRAINING PROGRAMS ON THE PERFORMANCE OF CIVIL SERVANTS MEDIATED BY WORK MOTIVATION AT THE DIRECTORATE OF INSTRUCTOR AND TRAINING PERSONNEL DEVELOPMENT - Desti Arianti; Zainul Kisman (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2026)
This study aims to analyze the effect of competency improvement and training programs on the performance of civil servants (ASN) and the role of work motivation as a mediating variable in the Directorate of Instructor and Training Personnel Development. ASN performance is an important factor in supporting the effectiveness of public organizations, thus requiring human resource management that emphasizes competency strengthening and the implementation of appropriate training programs. This study uses a quantitative approach with a survey method. The research population consists of all ASN employees, including civil servants and PPPK employees at the Directorate of Instructor and Training Personnel Development, with a census sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM). The results showed that competency improvement and training programs had a significant effect on ASN employee performance. Improvement also had a significant effect on work motivation, while training programs did not have a significant effect on work motivation. Furthermore, work motivation does not significantly affect the performance of ASN employees. The mediation test results show that work motivation does not mediate the effect of competency improvement and training programs on the performance of ASN employees. These findings indicate that the performance of ASN employees is more directly influenced by competency and training programs as actual work abilities and formal task fulfillment than by work motivation as a psychological incentive